2022
DOI: 10.1101/2022.07.26.501543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural integration and segregation revealed by a joint time-vertex connectome spectral analysis

Abstract: Brain oscillations are produced by the coordinated activity of large groups of neurons and different rhythms are thought to reflect different modes of information processing. These modes, in turn, are known to occur at different spatial scales. Nevertheless, how these rhythms support different modes of information processing at the brain scale is not yet fully understood. Here we present "Joint Time-Vertex Connectome Spectral Analysis", a framework for characterizing the spectral content of brain activity both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
(144 reference statements)
0
6
1
Order By: Relevance
“…We have shown in previous publications that the neuronal activity is sparsely represented by the connectome-based graph Fourier transform (see Connectome Spectral Analysis ), which decomposes brain activity into a small number of active brain networks [35, 34]. In addition to our research, other studies have established a theoretical basis for the structural constraint on functional connectivity [32, 36, 47, 48, 49]. These works have revealed that neural mechanisms relying on delayed excitatory-inhibitory interactions facilitate the self-organization towards exciting a relevant set of eigenmodes [32, 48].…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…We have shown in previous publications that the neuronal activity is sparsely represented by the connectome-based graph Fourier transform (see Connectome Spectral Analysis ), which decomposes brain activity into a small number of active brain networks [35, 34]. In addition to our research, other studies have established a theoretical basis for the structural constraint on functional connectivity [32, 36, 47, 48, 49]. These works have revealed that neural mechanisms relying on delayed excitatory-inhibitory interactions facilitate the self-organization towards exciting a relevant set of eigenmodes [32, 48].…”
Section: Methodsmentioning
confidence: 68%
“…These works have revealed that neural mechanisms relying on delayed excitatory-inhibitory interactions facilitate the self-organization towards exciting a relevant set of eigenmodes [32, 48]. Moreover, previous investigations have successfully applied structural eigenmodes to explain brain activity during rest at very short timescale [49] and evoked activity [47]. These findings suggest that these eigenmodes play a crucial role in dynamically integrating and segregating information across the cortex, thus serving important cognitive functions.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown in previous publications that the neuronal activity is sparsely represented by the connectome-based graph Fourier transform (see Connectome Spectral Analysis), which decomposes brain activity into a small number of active brain networks (Glomb et al, 2020;Rué-Queralt et al, 2021). In addition to our research, other studies have established a theoretical basis for the structural constraint on functional connectivity (Atasoy et al, 2016;Atasoy et al, 2018;Rue Queralt et al, 2022;Tewarie et al, 2019;Tewarie et al, 2022). These works have revealed that neural mechanisms relying on delayed excitatory-inhibitory interactions facilitate the self-organization toward exciting a relevant set of eigenmodes (Atasoy et al, 2016;Tewarie et al, 2019).…”
Section: Connectome Spectrum Electrical Tomography (Cset)mentioning
confidence: 65%
“…These works have revealed that neural mechanisms relying on delayed excitatory‐inhibitory interactions facilitate the self‐organization toward exciting a relevant set of eigenmodes (Atasoy et al, 2016 ; Tewarie et al, 2019 ). Moreover, previous investigations have successfully applied structural eigenmodes to explain brain activity during rest at very short timescale (Tewarie et al, 2022 ) and evoked activity (Rue Queralt et al, 2022 ). These findings suggest that these eigenmodes play a crucial role in dynamically integrating and segregating information across the cortex, thus serving important cognitive functions.…”
Section: Methodsmentioning
confidence: 99%
“…in Griffa and Preti, 2022;Preti and Van De Ville, 2019) or as the average connectivity matrix across the population (Rué-Queralt et al, 2023). Taken together, despite the important progress in probing the nature of structure-function coupling through the lens of task-based electrophysiological responses, the relationship between the continuous EEG and the underlying structural connectivity remains elusive.…”
Section: Methodsmentioning
confidence: 99%